Pengaruh Persepsi Mutu Pelayanan Kesehatan terhadap Tingkat Kepuasan Pasien di Puskesmas Senen Jakarta Pusat - Aisyah Maulina Sumbogo (Jurnal Medika Nusantara, 2025)
Puskesmas Senen in Central Jakarta, an outpatient health center, recorded the lowest number of patient visits in 2023, with only 80,643 visits among the 8 sub-district health centers in Central Jakarta. This decline may be attributed to a reduction in patient morbidity rates or suboptimal service quality. One way to assess the quality of service is through the SERVQUAL model, which includes responsiveness, assurance, physical evidence, empathy, and reliability. This study aimed to examine how the perceived quality of healthcare services impacts patient satisfaction levels at Puskesmas Senen. The research used an analytic survey design with a cross-sectional approach. A total of 363 respondents were selected using purposive sampling. The results indicated that responsiveness (p=0.044), tangible aspects (p=0.019), and empathy (p=0.008) significantly influenced patient satisfaction. In contrast, factors such as age (p=0.384 and 0.338), gender (p=1.000), education (p=0.720), occupation (p=0.933), assurance (p=0.227), and reliability (p=0.237) did not have a significant effect on patient satisfaction. The study concluded that the empathy dimension had the greatest impact on patient satisfaction at Puskesmas Senen, Central Jakarta.